Hemophagocytic lymphohistiocytosis associated with visceral leishmaniasis. Review of cases reported - Garrido, David Israel; Fuseau, Michelle; Garrido, Santiago; Celi, Santiago (Revista Cubana de Medicina Tropical, 2020)
Introduction: Leishmaniasis is a tropical and subtropical disease highly reported in Southeast Asia, East Africa, Latin America, and the Mediterranean basin, with an incidence of two million new cases by year and 500,000 cases of visceral leishmaniasis. One of the more severe and rare complications of visceral leishmaniasis is hemophagocytic lymphohistiocytosis. Objective: To describe the clinical characteristics of hemophagocytic lymphohistiocytosis associated with visceral leishmaniasis Methods: We performed a literature review based on the case reports indexed in MEDLINE/PubMed. Results: Twenty-five cases were included; 52 % under two years of age. All cases presented splenomegaly and 84% hepatomegaly. Cytopenias were described in all patients: 100% thrombocytopenia, 96% anemia, and 84% leukopenia or neutropenia. Hypertriglyceridemia and hypofibrinogenemia were found in 68% and 32%, respectively, and hyperferritinemia in 80%. Additionally, hemophagocytosis was documented in 84%, with Leishmania detection in 92%. All patients were treated against Leishmania: 80% with liposomal amphotericin B. regarding the treatment for hemophagocytic lymphohistiocytosis; corticosteroid were used in 36%, endovenous immunoglobulin in 28%, cyclosporine in 28% and etoposide in 16% The complications reported included gastrointestinal hemorrhage (8%), disseminated intravascular coagulation (8%), autoimmune hemolytic anemia (12%), multiple-organ dysfunction/septic shock (12%), petechial rash (16%), and four patients deceased. Variables such as fever (p=0.031), hemoglobin level (p=0.031), platelet count (p=0.0048), and ferritin (p=0.0072) were associated with mortality Conclusions: During visceral leishmaniasis, the hemophagocytic syndrome is a rare condition that mainly affects pediatric patients, but with excellent outcomes using liposomal amphotericin B. However, there is a lack of strong evidence to make a recommendation.